Pengaruh Karakteristik Pekerjaan terhadap Kepuasan Kerja Pegawai di Lingkungan Pemkot Payakumbuh - Firman, Firman (Fakultas Ilmu Sosial Universitas Negeri Padang, 2011)
ABSTRACT This study examines the relationship between of job characteristic encompassed by four components: (pay satisfaction and career growth, task clarity, skill utilization and task significant) with job satisfaction. The study investigated the relationship of these variables in the municipality of Payakumbuh. The data was collected through the distribution of questionnaires among 93 civil servants of number employees selected through a cluster random sampling. The study findings show that task clarity, skill utilization and task significant have significant relationship with job satisfaction. Kata Kunci: Karakteristik pekerjaan, kepuasan kerja, pegawai